A Retrospective Analysis Examining the Impact of Educational Attainment and Social Determinants of Health on Rifampicin-Resistant Tuberculosis Treatment Outcomes - Titilade Kehinde Ayandeyi Teibo; Rubeshan Perumal; Lateef Babatunde Amusa; Letitia Shunmugam; Nonkululeko Mzinyane; Darshan Chetty; Resha Boodhram; Radhamoney Narasimmulu; Takondwa Kachoka; Claudia Shozi; Max R O’Donnell; Allison Wolf; et al. (Open Forum Infectious Diseases, 2026)
Abstract Background Rifampicin-resistant tuberculosis (RR-TB) remains a major public health challenge in TB-endemic regions. While social determinants of health, including socioeconomic status, affect infectious disease outcomes, their impact on RR-TB remains poorly understood. This study evaluated the relationship between educational attainment, social disadvantage, and RR-TB outcomes. Methods We conducted a retrospective cohort study using data from four CAPRISA RR-TB clinical trials. Social vulnerability was measured using an exploratory Social Disadvantage Score (SDS) that incorporated education, employment, and incarceration. We used a latent class analysis (LCA) to identify classes with shared social vulnerability indicators. Associations with treatment outcomes were assessed using separate Cox regression models, with the exploratory SDS, its component indicators, and derived latent classes as predictors. Results Education was not independently associated with unfavourable treatment outcomes (aHR=1.39, 95% CI: 0.96–1.99, p=0.077), whereas a history of incarceration doubled the hazard (aHR=2.05, 95% CI: 1.33–3.16, p<0.001). Restricting subsequent models to the sub-cohort with collected employment data, unemployment increased the hazard of unfavourable outcomes (aHR=1.84, 95% CI: 1.20–2.82, p=0.005). Using the same sub-cohort, increasing cumulative social disadvantage showed a strong dose–response relationship, with a fivefold higher hazard for three disadvantages (aHR=5.85, 95% CI: 2.73–12.56, p < 0.001). LCA revealed that Class 2 (moderate socioeconomic advantage) had a significantly higher hazard of unfavourable outcomes (aHR=1.82, 95% CI: 1.19–2.79, p=0.006). Conclusion Cumulative social risk score was associated with unfavourable RR-TB outcomes. These findings support further evaluation of targeted support for disadvantaged populations to enhance RR-TB treatment success.